(untitled) (UNWE Yearbook, 2014)
The current study presents a critical analysis of the contemporary views on human resources development in organizations, whose conceptual fundamentals are related to the resource-based view of the firm as well as the theory of human capital, and from these standpoints a methodical framework for research approaches in this field is being developed. The study reveals the core characteristics of human resources development in organizations as a process for employees’ human capital improvement. Human resources development in organizations is being analyzed as a complicated amalgam of processes, realized on the individual and organizational levels, during which certain resources are being transformed into a result, benefiting not only the individuals and the organizations, but also society.